Successful Educational Administrators - Krissana Bulan กฤษณะ บุหลัน (Dusit Thani College Journal, 2018)
Successful Educational Administrators should convey organizational success to develop the competency for them and also to encourage for any employees including students. Furthermore, successful educational administrators attribute should be generated by 7 attributes such as strategic thinking, communication, teamwork, self-confidence, decision making on facts, focusing on content and emotional control. Therefore, it should be to hold the ultimate goal for success. The factors would be attended on “Self-control, People Control and Work Control” in balance, and also would contribute your organization to sustainable success.